A distinct judicial power the origins of an independent judiciary, 1606-1787 - Gerber, Scott Douglas, 1961- (Oxford : Oxford University Press, 2011)
This title provides a comprehensive critical analysis of the origins of judicial independence in the United States. The book examines the political theory of an independent judiciary and chronicles how each of the original 13 states and their colonial antecedents treated their respective judiciaries.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Judicial independence -- United States -- History; Judges -- United States; Judicial power -- United States